Report on the activities of the PAU Commission on the History of Science in 2020/2021 - Michał Kokowski (Studia Historiae Scientiarum, 2021)
The report discusses the activities of the Commission on the History of Science of the Polish Academy of Arts and Sciences in 2020/2021. It presents the lists of: scientific meetings, conferences, symposia, seminars, new members and new publications.